2019
DOI: 10.1183/23120541.00010-2019
|View full text |Cite
|
Sign up to set email alerts
|

Snoring and nocturnal reflux: association with lung function decline and respiratory symptoms

Abstract: IntroductionThe study aim was to examine the association of snoring and nocturnal gastro-oesophageal reflux (nGOR) with respiratory symptoms and lung function, and if snoring and/or nGOR associated with a steeper decline in lung function.MethodsData from the third visit of the European Community Respiratory Health Survey (ECRHS) was used for cross-sectional analysis. Pre- and post-bronchodilator spirometry was performed, and information on sleep, nGOR and respiratory symptoms was collected (n=5715). Habitual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…We have recently described that snoring is associated with a significant decline in lung function [9], and this study further validates that finding by also looking at reported nocturnal choking and apnoeas, other common OSA symptoms. We even found a negative linear relationship between the OSA symptom score and the decline in lung function, further supporting the relevance of this finding.…”
Section: Lung Function Declinesupporting
confidence: 86%
See 1 more Smart Citation
“…We have recently described that snoring is associated with a significant decline in lung function [9], and this study further validates that finding by also looking at reported nocturnal choking and apnoeas, other common OSA symptoms. We even found a negative linear relationship between the OSA symptom score and the decline in lung function, further supporting the relevance of this finding.…”
Section: Lung Function Declinesupporting
confidence: 86%
“…Habitual snoring has recently been described to be associated with a decline in lung function, indicating that OSA may play a role in lung function decline [9]. However, even though snoring and OSA are linked, not all habitual snorers have OSA [5].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding nGER, our previous studies have found an association between nGER and respiratory symptoms, especially among snorers and found persistent nGER to be a risk factor for developing respiratory symptoms 1 6 29. There are different theories on how nGER may cause respiratory symptoms, and different mechanisms may associate with different respiratory symptoms 8.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a relationship between various sleep disorders and respiratory symptoms ( 22 , 23 ). More respiratory symptoms were also present in people with habitual snoring ( 24 ). Bjornsdottir found that people with short sleep times reported more respiratory symptoms; not only that, they found that long sleep duration was associated with morning cough and dyspnea after activity ( 25 ).…”
Section: Discussionmentioning
confidence: 99%